2009
DOI: 10.1007/s00125-009-1484-7
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive function and risks of cardiovascular disease and hypoglycaemia in patients with type 2 diabetes: the Action in Diabetes and Vascular Disease: Preterax and Diamicron Modified Release Controlled Evaluation (ADVANCE) trial

Abstract: 2328 -2336 DOI 10.1007 /s00125-009-1484 scores 28-30 ('normal', n=8,689), 24-27 ('mild dysfunction', n=2,231) and <24 ('severe dysfunction', n=212). Risks of major cardiovascular events, death and hypoglycaemia and interactions with treatment were assessed using Cox proportional hazards analysis. Results Relative to normal function, both mild and severe cognitive dysfunction significantly increased the multipleadjusted risks of major cardiovascular events (HR 1.27, 95% CI 1.11-1.46 and 1.42, 95% CI 1.01-1.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
121
1
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(137 citation statements)
references
References 36 publications
5
121
1
6
Order By: Relevance
“…Glycemic targets in patients with "hypoglycemia unawareness" should be relaxed for prolonged periods, pending the potential reversal of the condition [58,59]. In patients with severe coexisting conditions that could interfere with implementation of the management strategy, the goal is prevention of clinically significant glycosuria, water and electrolyte loss, infections, and the development of non ketotic hyperosmolar coma.…”
mentioning
confidence: 99%
“…Glycemic targets in patients with "hypoglycemia unawareness" should be relaxed for prolonged periods, pending the potential reversal of the condition [58,59]. In patients with severe coexisting conditions that could interfere with implementation of the management strategy, the goal is prevention of clinically significant glycosuria, water and electrolyte loss, infections, and the development of non ketotic hyperosmolar coma.…”
mentioning
confidence: 99%
“…We excluded 87 because the association of baseline cognitive impairment and future stroke was not reported, 6 because most of the participants had a history of stroke at baseline, 3 because they were duplicate reports and 1 because no adjusted estimate was reported. 17 Our final primary analysis included 18 cohort studies [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] (Figure 1). Characteristics of the 18 included studies are shown in Table 1.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
“…Participants were derived from ordinary cohorts in 14 studies [18][19][20][22][23][24][25]27,[29][30][31][33][34][35] and clinical trials in 4. 21,26,28,32 Most of the studies were from North American or European countries. One was conducted in Taiwan, and 3 were an international collaboration.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…A different physiopathology involving small-vessel disease might also be involved in patients with clinical symptoms of dementia compatible with AD [37]. Furthermore, the ADVANCE trial stratified participants according to their mini-mental state examination (MMSE) score of 28-30, 24-27 and equal to or below 23 [38]. Comparisons between groups were made with regards to the incidence of cardiovascular events, death and the occurrence of hypoglycemia.…”
Section: Hypoglycemia In the Older Population: Is There A Difference mentioning
confidence: 99%